ChemInform Abstract: A Copper‐Mediated Tandem Reaction Through Isocyanide Insertion into N—H Bonds: Efficient Access to Unsymmetrical Tetrasubstituted Ureas. Issue 17 (28th April 2014) - Huang, Xiaomei; Xu, Shuguang; Tan, Qitao; Gao, Mingchun; Li, Minjie; Xu, Bin
Abstract The first Cu‐mediated multicomponent reaction proceeding through sequential isocyanide insertion into N—H bond, reductive elimination of CuH and 1, 3‐acyl transfer is demonstrated.